2012
DOI: 10.1371/journal.pone.0044824
|View full text |Cite
|
Sign up to set email alerts
|

Immune Complex Signatures of Patients with Active and Inactive SLE Revealed by Multiplex Protein Binding Analysis on Antigen Microarrays

Abstract: Systemic lupus erythematosus is characterized by dysfunctional clearance of apoptotic debris and the development of pathogenic autoantibodies. While the complement system is also involved in the disease no attempt has been made to generate a comprehensive view of immune complex formation from various autoantigens. We increased the complexity of autoantibody profiles by measuring the binding of two complement proteins, C3 and C4, in addition to two antibody classes, IgG and IgM, to a collection of autoantigens.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0
1

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 27 publications
(32 reference statements)
0
31
0
1
Order By: Relevance
“…Interestingly, the highest total number of different antigens recognized per sample was 88 for an OND plasma sample, whereas the lowest total number of different antigens recognized per sample, 16, was observed also for another OND sample. The median number across the cohort was 55 antigens recognized per sample.…”
Section: Resultsmentioning
confidence: 91%
See 1 more Smart Citation
“…Interestingly, the highest total number of different antigens recognized per sample was 88 for an OND plasma sample, whereas the lowest total number of different antigens recognized per sample, 16, was observed also for another OND sample. The median number across the cohort was 55 antigens recognized per sample.…”
Section: Resultsmentioning
confidence: 91%
“…Accordingly, the use of antigen microarrays for a multiparallel determination of antibody reactivity toward hundreds or thousands of antigens represents an appealing, high-throughput concept (79), especially if arrays can be built without biased target selection so that novel autoantigen candidates can be proposed. Antigen microarrays, either in planar or bead-based format, have recently been shown useful for autoantibody profiling in a range of diseases including, but not limited to, autoimmune diseases (1016). Regardless of whether the antigens are expressed followed by immobilization, or directly expressed on-site (17, 18), a resource of either protein antigens or cDNA clones is needed to build such arrays.…”
mentioning
confidence: 99%
“…However, despite these strict criteria, SLE is commonly misdiagnosed and mistreated, even by expert physicians [54]. The lack of validated autoantigen biomarkers to diagnosis SLE has prompted investigators to examine additional immunological features through traditional microarray on glass/nitrocellulose slides [55][59] to address this unmet need, including autoantibodies targeting self-peptides [54].…”
Section: Discussionmentioning
confidence: 99%
“…Papp et al demonstrated that the potential pathological impact of ICs is also dependent on the IC signature, the antibody classes and subclasses and the antigen to which the ICs are directed to (Papp et al, 2012). Whereas IgG1 and IgG3 are strong complement activators, IgG-mediated complement activation of the classical pathway can be silenced and be manipulated by specific antibody isotypes which do not bind C1q, for example, IgG4 or IgA (Davies et al, 2014;Dechant and Valerius, 2001;Kerr, 1990;Labrijn et al, 2008;van der Neut et al, 2007;Woof and Kerr, 2006).…”
Section: C1q and Pathological Immunecomplexesmentioning
confidence: 99%